Media Influence: Students Creativity and Learning History Achievement of Universitas Syiah Kuala - Muhammad Fadhil (Universitas Syiah Kuala, 2021)
This study aims: to determine the effect of the application of the Gallery of Learning the learning achievement of students of Universitas Syiah Kuala. This study uses a quantitative approach and the type of experimental research. The population in this study are students of history education, amounting to 46 people. This research data collection techniques using tests and documentation. As for the stage of data analysis techniques in this study were; (1) calculate the average; (2) calculate the variance and standard deviation; (3) test for normality data; (4) test of homogeneity of variance; and t-test. Based on the data analysis stage it is obtained:Final test homogeneity of variance test experiment and control class was 1.53 and 0.49 t-test results. Results of research found is the implementation strategy of lear(gallery of learning) effect on student learning achievement history educationhistory of Universitas Syiah Kuala. Data Distribution final test scores of students in the experimental and control group with normal distribution based on a significant level ≤ X2countX2 tablenamely 7.81 and 4.51 ≤ 4.93 ≤ 7.81, to test the homogeneity of F ≤ 1.53 ≤ 2.03 Ftabel = then the data variance experimental class and control class homogeneous. The results of t-test to analyze the effect of learning outcomes by using strategies learned gallery acquired the t-test is t = 0.49, while table = 1.68. Means that t ≥ 1.68 ≥ table = 0.49.